A Medical Student’s Perspective on the Growing Importance of Telemedicine/Telerehabilitation - Park, Sung-Hoon; Yozbatiran, Nuray (International Journal of Medical Students, 2022)
Telemedicine, particularly telerehabilitation for patients with chronic conditions such as spinal cord injury (SCI), has greatly evolved in the 21st century and expanded rapidly during the COVID-19 pandemic. Rehabilitation programs aiming to improve motor functions after SCI are important in reducing disability, promoting independence, and alleviating burden of caretakers. An appropriate intervention is limited to many patients due to requirements of periodic access to a location with appropriate equipment as well as a therapist to facilitate a one-on-one session to improve upper limb functions. Therefore, telerehabilitation can increase access to appropriate interventions to improve upper limb functions. This paper shows the limitations and benefits as well as the potential future of telerehabilitation based on a summertime experience of a rising 2nd year medical student.